SK-languages as a Powerful and Flexible Semantic Formalism for the Systems of Cross-Lingual Intelligent Information Access (Informatica, 2017)
The first starting point of this paper is the broadly accepted idea of employing, as a promising methodology, an artificial semantic language-intermediary for the realization of automatic cross-lingual intelligent information access to natural language (NL) texts on the Web. The second one is the emergence in computational semantics during 2013-2016 of great interest in the semantic formalism (more exactly, notation) called Abstract Meaning Representation (AMR). This formalism was introduced in 2013 in an ACL publication by a group consisting of ten researchers from UK and USA. This paper shows that much broader prospects for creating semantic languages-intermediaries in comparison with AMR are opened by the theory of K-representations (TKR), developed by V. A. Fomichov. The basic mathematical model of TKR describes the regularities of NL structured meanings. The mathematical essence is that this model introduces a system consisting of ten partial operations on conceptual structures. Initial version of this model was published in 1996 in Informatica (Slovenia). The second version of the model (stated in a monograph released by Springer in 2010) defines a class of formal languages called SK-languages (standard knowledge languages). It is demonstrated that SK-languages allow us to simulate all expressive mechanisms of AMR. The advantages in comparison with AMR are, in particular, the possibilities to construct semantic representations of compound infinitive constructions (expressing goals, commitments, etc), of compound descriptions of notions and sets, and of complex discourses and knowledge pieces.